Sarcoidosis and Cancer: A Complex Relationship - El Jammal, Thomas; Pavic, Michel; Gerfaud-Valentin, Mathieu; Jamilloux, Yvan; Sève, Pascal (Frontiers in Medicine, 2020)
Sarcoidosis is a systemic disease of unknown etiology, characterized by the presence of noncaseating granulomas in various organs, mainly the lungs and the lymphatic system. Since the individualization of sarcoidosis-lymphoma association by Brincker et al. in 1986, the relationship between sarcoidosis or granulomatous syndromes and malignancies has been clarified through observational studies worldwide. Two recent meta-analyses showed an increased risk of neoplasia in sarcoidosis. Granulomatosis can also reveal malignancy, either solid or hematological, defining paraneoplastic sarcoidosis. Recent cancer immunotherapies, including immune checkpoint inhibitors (targeting PD-1, PD-L1, or CTLA-4) and BRAF or MEK inhibitors were also reported as possible inducers of sarcoidosis-like reactions. Sarcoidosis and neoplasia, especially lymphoma, can show overlapping presentations, thus making the diagnosis and treatment harder to deal with. There are currently no formal recommendations to guide the differential diagnosis work-up between the evolution of lymphoma or a solid cancer and a granulomatous reaction associated with neoplasia. Thus, in atypical presentations (i.e. deeply impaired condition, compressive lymphadenopathy, atypical localization, unexplained worsening lymphadenopathy or splenomegaly), and treatment-resistant disease, targeted biopsies on suspect localizations with anatomopathological examination could help the clinician to differentiate neoplasia from sarcoidosis. Pathological diagnosis could sometimes be challenging since very few tumor cells may be surrounded by massive granulomatous reaction. The sensitization of currently available diagnostic tools should improve the diagnostic precision, such as the use of more “cancer-specific” radioactive tracers coupled with Positron Emission Tomography scanner.